Ultra-Transparent and Multifunctional IZVO Mesh Electrodes for Next-Generation Flexible Optoelectronics - Nirmal, Kiran A.; Dongale, Tukaram D.; Khot, Atul C.; Yao, Chenjie; Kim, Nahyun; Kim, Tae Geun (Nano-Micro Letters, 2024)
Mechanically durable transparent electrodes are essential for achieving long-term stability in flexible optoelectronic devices. Furthermore, they are crucial for applications in the fields of energy, display, healthcare, and soft robotics. Conducting meshes represent a promising alternative to traditional, brittle, metal oxide conductors due to their high electrical conductivity, optical transparency, and enhanced mechanical flexibility. In this paper, we present a simple method for fabricating an ultra-transparent conducting metal oxide mesh electrode using self-cracking-assisted templates. Using this method, we produced an electrode with ultra-transparency (97.39%), high conductance (Rs = 21.24 Ω sq−1), elevated work function (5.16 eV), and good mechanical stability. We also evaluated the effectiveness of the fabricated electrodes by integrating them into organic photovoltaics, organic light-emitting diodes, and flexible transparent memristor devices for neuromorphic computing, resulting in exceptional device performance. In addition, the unique porous structure of the vanadium-doped indium zinc oxide mesh electrodes provided excellent flexibility, rendering them a promising option for application in flexible optoelectronics. Highlights: 1 Ultra-transparent vanadium-doped indium zinc oxide mesh (mIZVO) electrodes are fabricated using a self-cracking template. 2 Fabricated electrodes are employed to realize flexible organic solar cell (OSC), organic light-emitting diode (OLED), and memristor devices. OSC exhibits 14.38% power conversion efficiency and OLED achieves 18.06% external quantum efficiency with mIZVO electrode. 3 Flexible-transparent memristor based on mIZVO mimics various synaptic functions.